COMPARISON OF THERAPY GUIDED IMAGERY WITH SLOW DEEP BREATHING RELAXATION IN REDUCE PLEASE PATIENT SCALE LAPARATOMI IN SEMICIDE ROOM ULIN BANJARMASIN 2017 - Izma Daud; Muthmainnah Muthmainnah (Universitas Muhammadiyah Banjarmasin, 2018)
Surgical action is always associated with incisions / incisions that are traumatic or violent to the patient who cause various complaints and symptoms. One of the most common complaints is pain (Sjamsuhidajat and Jong, 2005). Guided imagery is a technique that uses the imagination of an individual with a guided imagination to reduce stress. This study aims to determine the effect of combination therapy of slow deep breathing and guided imagery relaxation on the scale of pain in patients post laparatomi surgery. Method: Using Quasi Experiment pre post test, sample of intervention group 33 respondents and control group 33 respondents. The intervention group was given combination therapy of slow deep breathing and guided imagery relaxation and analgetic according to room SOP and control group only given analgetic according to room SOP. Data analysis using Mann-Whitney Test with 95% confidence degree. Results: There was a significant difference in mean pain scale before and after the intervention of Slow deep breathing Relaxation, and there was also a significant difference in mean postoperative pain scale of laparotomy before and after intervention in the guided imagery group.